STUDY ON FUNCTION FACILITIES UTILIZATION OF PALABUHANRATU FISHING PORT AT WEST SUMATERA PROVINCE - Ekariski, Rima Stefi; ', Syafruddin; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this research is to know the utilization of functional facility ofFishery Port of Nusantara Palabuhanratu. This research was conducted in March untilApril 2017. The method used in this research is survey method at fishery port ofPalabuhanratu archipelago. Data analysis using technical analysis (facility requirementanalysis) and facility utilization analysis. The survey shows that existing functionalfacilities include workshops, fishing gear improvements, docking venues, fish auctionsites, freshwater tanks, fuel tanks and bulk ice factories. Of the 7 existing facilities, only 3facilities can be analyzed. Based on the results of the analysis can be seen that the level ofneed for fish auction place is 3.40% classified as less good, freshwater tank is 1.25%classified as less good, and fuel tank is 2.23% classified as less good.Keywords: fishing port, functional facilities, utilization level